Investigative Comittees during “Revolución Libertadora”. Archive usages on the historiography about Peronism and anti-Peronism (Quinto Sol, 2016)
This article highlights and portrays the features of the document collection of the National Investigative Committee. This institution was created in 1955 during “Revolución Libertadora” in order to investigate alleged irregularities during the administration that they themselves had overthrown and became one of the emblems of political persecution against Peronism. A broad overview on its structure, as well as the documentation produced, is a first contribution of this article. Secondly, we track how different parts of the corpus (files, memories, the Black Book) have been used for historical reconstruction. Away from the idea of the archive as neutral territory, our goal is to identify the ambiguous ties linking the process of investigative committees, its documents and the uses that we have given professional historians. Articulating elements proper to empirical research with theoretical and historiographical tools, this reflection constitutes a starting point to build an agenda of issues concerning “desperonización”.The approach seeks to focus on a “from the bottom up” perspective based on the analysis of judicial records. The general aim is to construct a more experiential interpretation of the Peronism-anti-Peronism conflict.
Keywords: archive; peronism; “Revolución Libertadora”; National Investigative Committee; judicial records